Kepemimpinan Integral dan Modernisasi Holistik: Analisis Komprehensif Peran Imam Zarkasyi dalam Pembentukan Pendidikan Islam di Pondok Pesantren 'Darussalam' Gontor - Bahij, Muhammad Alfan; Khoir, Mulyanto Abdullah (TSAQOFAH, 2024)
This research delves into the role of Imam Zarkasyi in the modernization of "Darussalam" Islamic Boarding School in Gontor, focusing on the integration of formal, non-formal, and informal education. Two main issues are addressed: the impact of Imam Zarkasyi's leadership on the modernization process of the pesantren and the relevance of this model at the national level. Imam Zarkasyi's holistic approach includes balancing religious and general knowledge, promoting self-directed learning, and institutional transformation through public ownership and endowments. Four problem-solving plans are proposed to strengthen the modernization of Islamic education in Gontor, including improving accessibility, developing innovative curricula, utilizing technology, and enhancing teaching quality. The theoretical study highlights the holistic contributions of Imam Zarkasyi in shaping Islamic education in Indonesia. The research aims to conduct a comprehensive analysis of Imam Zarkasyi's role, focusing on integral leadership, educational integration, and institutional transformation. The research method employs a qualitative approach with a case study at "Darussalam" Islamic Boarding School in Gontor. Thematic data analysis is performed with verification through triangulation of data sources. Findings indicate Imam Zarkasyi's positive role in the modernization of the pesantren and its sustainable impact. Keywords: